1972
DOI: 10.1071/bi9720023
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Aleurone Layer I. Oonventional and Fluorescence Microscopy of the Cell Wall With Emphasis on Phenol-Carbohydrate Complexes in Wheat

Abstract: In the ungerminated seed, the cell walls of the aleurone layer of wheat (Triticum aestivum cv. Heron) are strongly autofluorescent and are stained by aniline blue, resorcinol blue, toluidine blue, and the periodic acid-Schiff's reaction. Thin-layer chromatography of acid or alkaline extracts and microspectrofluorimetry indicate that the fluorescent component of the wall is ferulic acid. During germina-tion, the ferulic acid disappears from the aleurone cell wall in a specific pattern and its loss is accompanie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
47
0
2

Year Published

1987
1987
2012
2012

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(56 citation statements)
references
References 12 publications
7
47
0
2
Order By: Relevance
“…Of these, ferulic acid was the primary phenolic acid in the grain, accounting for up to 90% of total phenolic acids [60,62,70,91,103,108]. Ferulic acid is found, predominantly, in the aleurone cell walls of kernel [67,109,110] and it is esterified to arabinose [111,112], stanols and sterols [95] and glucose [113]. Campestanyl and sitostanyl ferulates were the main steryl ferulates present in wheat grain [114].…”
Section: Phenolics In Cerealsmentioning
confidence: 99%
“…Of these, ferulic acid was the primary phenolic acid in the grain, accounting for up to 90% of total phenolic acids [60,62,70,91,103,108]. Ferulic acid is found, predominantly, in the aleurone cell walls of kernel [67,109,110] and it is esterified to arabinose [111,112], stanols and sterols [95] and glucose [113]. Campestanyl and sitostanyl ferulates were the main steryl ferulates present in wheat grain [114].…”
Section: Phenolics In Cerealsmentioning
confidence: 99%
“…Growing evidence indicates that intake of whole grain-based foods may contribute to health benefits including the reduced risk of certain type of cancers and coronary heart diseases (Jacobs, Marquart, Slavin, & Kushi, 1998). Several studies have investigated the antioxidant properties, and nutritional and phytochemical compositions of wheat grain or its milling fractions (Fulcher, O'brien, & Lee, 1972;Liyana-Pathirana & Shahidi, 2007; Mateo Anson, Van den Berg, & Havenaar, 2008;Moore et al, 2005;Okarter, Liu, Sorrells, & Liu, 2010;Yu, Perret, Harris, Wilson, & Haley, 2003;Zhou, Laux, & Yu, 2004). These previous studies also indicated that different wheat genotype, growing environment, and the interaction between genotype and environment may significantly alter the health properties in wheat grain.…”
Section: Introductionmentioning
confidence: 96%
“…In the case of wheat grain, exploration of the walls by light and electron microscopy (Fulcher et al 1972;Mares and Stone 1973;Bacic and Stone 1981;Fulcher 1982), microspectroXuorometry (Akin 1995;Saadi et al 1998) and vibrational microspectroscopy (Piot et al 2000(Piot et al , 2001 showed that the cell walls were highly heterogeneous in terms of morphology and composition, especially regarding phenolic acids (Akin 1995;Saadi 1998;Piot et al 2001). However, UV and Xuorescence techniques lack speciWcity regarding the phenolic components.…”
Section: Introductionmentioning
confidence: 97%